A Simple Options Trading Strategy based on Technical Indicators - Carlier, Francesco (International Journal of Economics and Financial Issues, 2021)
This paper is devoted to research the validity of options strategies with a particular emphasis on weekly options. The author proves that options, when traded successfully, could be a better substitute than buying or selling the underlying and that options with a good given volatility strategy and with a well capitalised underlying stocks could give superb results. The author analysed a simple strategy using the simple moving average and the bollinger bands on the US market. Then a new capital allocation method is explained with the target of maximizing the results obtained. For further comparison the options strategy is compared with the same strategy made with selling or buying the underlying. Keywords: Financial markets, options, technical analysis indicators JEL Classifications: G11; G15; G24 DOI: https://doi.org/10.32479/ijefi.11144